Uphill and downhill charge generation from charge transfer to charge separated states in organic solar cells. Issue 40 (6th October 2021) - Alam, Shahidul; Nádaždy, Vojtech; Váry, Tomáš; Friebe, Christian; Meitzner, Rico; Ahner, Johannes; Anand, Aman; Karuthedath, Safakath; De Castro, Catherine S. P.; Göhler, Clemens; Dietz, Stefanie; Cann, Jonathan; et al.
Abstract : Energy level alignments at the organic donor–acceptor interface cannot be predicted from cyclic voltammetry. Onsets for joint density of states and charge generation, reveal cases of energy uphill and – newly observed – downhill charge generation. Abstract : It is common knowledge that molecular energy level offsets of a type II heterojunction formed at the donor–acceptor interface are considered to be the driving force for photoinduced charge transfer in organic solar cells. Usually, these offsets – present between molecular energy levels of the donor and acceptor – are obtained via cyclic voltammetry (CV) measurements of organic semiconductors cast in a film or dissolved in solution. Simply transferring such determined energy levels from solution or film of single materials to blend films may be obviously limited and not be possible in full generality. Herein, we report various cases of material combinations in which novel non-fullerene acceptors did not yield successful charge transfer, although energy levels obtained by CV on constituting single materials indicate a type II heterojunction. Whilst the integer charge transfer (ICT) model provides one explanation for a relative rise of molecular energy levels of acceptors, further details and other cases have not been studied so far in great detail. By applying energy-resolved electrochemical impedance spectroscopy (ER-EIS) on several donor–acceptor combinations, a Fano-like resonance feature associated with a distinctive molecular energy level of the acceptor as well as various relative molecular energy level shifts of different kinds could be observed. By analyzing ER-EIS and absorption spectra, not only the exciton binding energy within single materials could be determined, but also the commonly unknown binding energy of the CT state with regard to the joint density of states (jDOS) of the effective semiconductor. The latter is defined by transitions between the highest occupied molecular orbitals (HOMO) of the donor and the lowest unoccupied molecular orbitals (LUMO) of the acceptor. Using this technique among others, we identified cases in which charge generation may occur either via uphill or by downhill processes between the charge transfer exciton and the electronic gap of the effective semiconductor. Exceptionally high CT-exciton binding energies and thus low charge generation yields were obtained for a case in which the donor and acceptor yielded a too intimate blend morphology, indicating π–π stacking as a potential cause for unfavorable molecular energy level alignment.